PENGENDALIAN KUALITAS PRODUK DENGAN PENDEKATAN SIX SIGMA PADA PT. KAYABA INDONESIA - Raden Bimantyo Satrio Jatmiko (2022)
The impact of globalization in today's industrial world makes competition between companies increasingly tight and competitive. At PT. XYZ is known that the number of defects in the company has not reached the target given by the customer. At PT. Kayaba Indonesia has products that have a high intensity in customer claims , which are products manufactured for automobiles. Based on claim per customer, there are customers who made claims in the last 6 months, including PT. Toyota Motor Manufacturing, PT. XYZ, PT. Mitsubishi Motors Krama Yudha Indonesia, and PT. Hino Motors Manufacturing Indonesia The target given is a target that is close to zero defects. When compared with the actual number of defects, it is necessary to improve and control the production process. The purpose of this study is to identify Critical to Quality in the production process and then determine the priority of the factors that cause defects in production using the Six Sigma. The results of this study indicate that based on the results of the DPMO calculation and the sigma level after implementation, the DPMO value has decreased to 3832,2. That is, there are 3832,2 defects in one million opportunities and the level of sigma also increased to 4,16764 sigma, where the level of sigma before the repair was carried out was 4,09386 sigma. Sigma level increased by 0,07378.